Characterization of NMB, GRP and their receptors (BRS3, NMBR and GRPR) in chickens. (July 2017) - Mo, Chunheng; Huang, Long; Cui, Lin; Lv, Can; Lin, Dongliang; Song, Liang; Zhu, Guoqiang; Li, Juan; Wang, Yajun
Abstract : The two structurally and functionally related peptides, gastrin-releasing peptide (GRP) and neuromedin B (NMB) play critical roles in many physiological/pathological processes in mammals. However, the information regarding the expression and functionality of avian NMB, GRP and their receptors is limited. Here, we characterized cNMB, cGRP and their receptors (cNMBR, cGRPR and cBRS3) in chickens. Our results showed that: (1) cNMBR and cGRPR expressed in CHO cells could be potently activated by cNMB and cGRP, respectively, as monitored by cell-based luciferase reporter assays, indicating that cNMBR and cGRPR are cNMB- and cGRP-specific receptors; strikingly, BRS3 of chickens (/spotted gars), which is orthologous to mouse bombesin receptor subtype-3 (BRS3), could be potently activated by GRP and NMB, demonstrating that both peptides are the endogenous ligands for chicken (/spotted gar) BRS3; (2) quantitative real-time PCR (qPCR) revealed that cGRPR is widely expressed in chicken tissues with abundant expression in the ovary, pancreas, proventriculus, spinal cord and brain, whereas cNMB, cNMBR and cBRS3 are mainly expressed in the brain and testes; (3) interestingly, qPCR, Western blot and immunostaining revealed that cGRP is predominantly expressed in the anterior pituitary and mainly localized to LH-cells, suggesting that cGRP is likely a novel pituitary hormone in chickens. In summary, our data help to uncover the roles of GRP, NMB and their receptors in birds, and provide the first persuasive evidence from an evolutionary prospective that in vertebrates, GRP and NMB are the endogenous ligands for BRS3, an orphan receptor that has puzzled endocrinologists for more than two decades.